2021
DOI: 10.1016/j.scitotenv.2020.143329
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNA detection and persistence in wastewater samples: An experimental network for COVID-19 environmental surveillance in Padua, Veneto Region (NE Italy)

Abstract: Background Clinical detection of SARS-CoV-2 RNA in stools supports the idea of wastewater-based epidemiology (WBE) as a precious tool for COVID-19 environmental surveillance. Successful detection of SARS-CoV-2 RNA in untreated wastewaters has been reported in several countries. This study investigated the presence and persistence of viral RNA in treated and untreated wastewaters in Padua, Italy. An urban experimental network of sampling sites was tested for prospective surveillance activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 25 publications
4
84
0
Order By: Relevance
“…Recent studies indicate the SARS-CoV-2 was rather stable at 4°C for at least 14 days [64] , [91] . The persistence of SARS-CoV-2 RNA after 24 h storage at 4°C was demonstrated with the same positive ratio before and after storage though the actual concentration of RNA detected was not reported [77] . A storage time within 48-72 hours is highly recommended to avoid the decay of SARS-CoV-2 RNA in wastewater [86] .…”
Section: Key Uncertainties For Estimating Sars-cov-2 Prevalence‘mentioning
confidence: 59%
See 1 more Smart Citation
“…Recent studies indicate the SARS-CoV-2 was rather stable at 4°C for at least 14 days [64] , [91] . The persistence of SARS-CoV-2 RNA after 24 h storage at 4°C was demonstrated with the same positive ratio before and after storage though the actual concentration of RNA detected was not reported [77] . A storage time within 48-72 hours is highly recommended to avoid the decay of SARS-CoV-2 RNA in wastewater [86] .…”
Section: Key Uncertainties For Estimating Sars-cov-2 Prevalence‘mentioning
confidence: 59%
“…With the recent development of detection methods, 13 available primer-probe sets, targeting regions and cycling parameters were further summarized (Table S2). Among these primer and probe sets, inconsistent performance between different primer-probe sets was commonly observed [27] , [75] , [77] , [80] , [98] . For instance, using the same wastewater samples, a higher positive ratio was detected with CDC N1 assays (19/63) than in E_Sarbeco assays (2/63) [75] .…”
Section: Key Uncertainties For Estimating Sars-cov-2 Prevalence‘mentioning
confidence: 99%
“…2.5 gc/μL. Nevertheless, some authors suggested a possible differential performance between the N and the Orf1b assay, with N showing a 10× sensitivity in both clinical and environmental samples ( Chu et al, 2020 ; Baldovin et al, 2020 ). The above described processes are graphically represented in the flow chart of Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This, in return, has raised the concern of having the wastewater, if not properly treated, as a tool to transmit and hence increase the SARS-CoV-2 spread and infection ( Gonzalez et al, 2020 ). Baldovin et al have analyzed samples from different wastewater points such as pumping station, wastewater treatment plant inlet, and outlet and found that SARS-CoV-2 RNA was present in both untreated and treated wastewater, with persistence up to 24 h in samples kept at 4 o C ( Baldovin et al, 2020 ). The relatively long half-life span of the SARS-CoV-2 of about 3 days in sewage systems and 3-4 in solid feces have been the main concern, as it can result in the increased spread and infection rate ( Nghiem et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%